TINGKAT KEPUASAN LAYANAN PENDIDIKAN MAHASISWA DAN ALUMNI FITK UIN SYARIF HIDAYATULLAH JAKARTA - Zaharil Anasy; Fauzan Fauzan; M Anang Jatmiko (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2019)
This study aims to determine the satisfaction of students and alumni FITK UIN education services Syarif Hidayatullah Jakarta. This research is a descriptive study with a quantitative approach. The population of this research is the 2014-2017 student class of FITK UIN Syarif Hidayatullah Jakarta. The sampling technique is done by propotionate stratified random sampling. The sample size was 354 students and 273 alumni. Data collection techniques using attitude scale. The data analysis technique is using trend test and percentage of frequency distribution. The results of this study indicate: 1) Educational services for students within the Faculty of Tarbiyah and Teacher Training (FITK) UIN Syarif Hidayatullah Jakarta in general are already good. The results are shown by questionnaire analysis on 46 statements which are mostly included in the category of very satisfied. Then the results of the percentage of student satisfaction with educational services which also has a value of 85.71% or in the category of very satisfied, 2) Educational services according to alumni in the Faculty of Tarbiyah and Teacher Training (FITK) UIN Syarif Hidayatullah Jakarta in general are already good. These results are shown by questionnaire analysis on 46 statements, most of which fall into the category of very satisfied. Then the results of the percentage of alumni satisfaction with education services which also has a value of 85.58% or in the category of very satisfied.